PENGARUH INDEPENDENSI, DUE PROFESIONAL CARE, PENGALAMAN, KOMPETENSI DAN KETERLIBATAN PIMPINAN TERHADAP KUALITAS AUDIT - Setyo Prabowo, 08.05.52.0097 Abimael; Indarti, Kentris (Students Journal of Accounting and Banking, 2012)
This study aims to examine the effect of independence, due professional care, experience and competence to audit the quality of audit in public accounting firm in the city of Semarang. Population is the auditor who worked on the Public Accountant in Hyderabad on 15 public accounting firm, with a sample of 47 respondents. Techniques used in the sampling inthis study is purposive sampling method, which is a technique of determining the sample with a certain consideration.Analysis tools used in this study were multiple linear regression, which previously tested the validity and reliability, the assumptions of normality and classical. Based on the test results indicate that the effect of auditor independence on audit quality showed a significant positive, meaning the higher the independence of the auditor, the auditor will affect the increase in the quality of the xamination. Due care professionals to audit quality issignificantly positive, meaning that the auditor usesprofessional skeptical attitude in the audit process, the more it will improve the quality of audit.Auditing experience a positive effect on audit quality, which means the higher the level of audit experience, the more it will improve the quality of audit in examinations. There is a positive influence on the competence of quality audit, which means that the higher the competence of the auditors the more it will improve the quality of audit. KAPled involvement of audit quality is significantly positive, meaning that the higher involvement of the leaders of public accounting firm, the more it will improve the quality of audit.Keywords: Independence, Due Professional Care, Audit Experi ence, Competence, Involvement of quality audit office and quality audit.